2010
DOI: 10.1055/s-0030-1250477
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anti-Melanogenic Steroidal Saponin Glycosides from Fenugreek (Trigonella foenum-graecumL.) Seeds

Abstract: Fenugreek seed ( Trigonella foenum-graecum L.) is used as an herbal medicine for treating metabolic and nutritive dysfunctions. To determine if this plant has other beneficial effects, we tested the inhibitory activities of a methanol (MeOH) extract of fenugreek seed on the production of inflammatory cytokines and melanin synthesis in cultured cell lines in vitro. The MeOH extract inhibited the production of phorbol-12-myristate-13-acetate-induced inflammatory cytokines such as tumor necrosis factor (TNF)-α in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 18 publications
0
48
0
2
Order By: Relevance
“…17) Proanthocyanidin oligomers have a variety of biological effects, including anti-allergic 8,18) and anti-oxidative activity. 19) Kolodziej et al, 20) have reported that 17 proanthocyanidins (types B and C) strongly suppressed the production of nitric oxide, TNF, and interferon (IFN)-γ in a cultured murine macrophage cell line (RAW 264.7) co-stimulated with INF-γ and LPS. In our study, some type A proanthocyanidins, especially compound 4 from peanut skin, strongly suppressed the production of inflammatory cytokines, whose activities were stronger than that of proanthocyanidin B-3 (9).…”
Section: Discussionmentioning
confidence: 99%
“…17) Proanthocyanidin oligomers have a variety of biological effects, including anti-allergic 8,18) and anti-oxidative activity. 19) Kolodziej et al, 20) have reported that 17 proanthocyanidins (types B and C) strongly suppressed the production of nitric oxide, TNF, and interferon (IFN)-γ in a cultured murine macrophage cell line (RAW 264.7) co-stimulated with INF-γ and LPS. In our study, some type A proanthocyanidins, especially compound 4 from peanut skin, strongly suppressed the production of inflammatory cytokines, whose activities were stronger than that of proanthocyanidin B-3 (9).…”
Section: Discussionmentioning
confidence: 99%
“…Anticarcinogenic activity was shown by a variety of steroidal saponins from different plants including Digitalis trojana (Kirmizibekmez et al 2014), Allium schoenoprasum (Timité et al 2013), Dioscorea zingiberensis (Tong et al 2012), Fagonia indica (Waheed et al 2012), Rhizoma Paridis (Xiao et al 2012), Solanum violaceum (Yen et al 2012), Agave sisalana (Chen et al 2011a, b), Anemarrhena asphodeloides (Kang et al 2011), Dioscorea bulbifera , Trigonella foenum-graecum (Kawabata et al 2011), Paris polyphylla (Zhu et al 2011), Raphia farinifera (Tapondjou et al 2015) etc.…”
Section: The Value Of Steroidal Saponinsmentioning
confidence: 99%
“…10 Fenugreek seeds also have an anti-inflammatory property that has been cited by several reports. 11,12 A previous study carried out by our laboratory has shown that after Al treatment, fenugreek seeds showed an anti-peroxidative effect in the posterior brain that was correlated to its antioxidant activity. 13 Relying on this preliminary result, as well as on the presumed anti-inflammatory property of this plant and the contribution of antioxidants in this phenomenon, we have chosen to investigate the neuroprotective effect of fenugreek seeds.…”
Section: Introductionmentioning
confidence: 93%